A Pilot Study of a Parent Emotion Socialization Intervention: Impact on Parent Behavior, Child Self-Regulation, and Adjustment - Bølstad, Evalill; Havighurst, Sophie S.; Tamnes, Christian K.; Nygaard, Egil; Bjørk, Rune Flaaten; Stavrinou, Maria; Espeseth, Thomas (Frontiers in Psychology, 2021)
Adequate emotion regulation in children is crucial for healthy development and is influenced by parent emotion socialization. The current pilot study aimed to test, for the first time in a Scandinavian population, whether an emotion-focused intervention, Tuning in to Kids (TIK), had positive effects on parent emotion-related socialization behaviors (ERSBs), and children’s self-regulation, internalizing and externalizing behavior problems. We conducted a controlled trial of the six-week evidence-based TIK parenting program with 20 parents of preschool children aged 5-6 years and 19 wait-list controls. Assessments at baseline and six months after the intervention included parent-report questionnaires on parent ERSBs and child adjustment, as well as aspects of children’s self-regulation assessed with two behavioral tasks, the Emotional Go/No-Go task (EGNG) and the AX-Continuous Performance Task (AX-CPT). Results showed a significant increase in reported parent emotion coaching behavior and an uncorrected significant decrease in child externalizing problems in intervention participants compared to controls. The behavioral data showed an uncorrected significant improvement in child emotion discrimination in the control condition compared to the intervention condition, while measures of children’s executive control improved from baseline to follow-up for both conditions but were not significantly different between conditions. These findings suggest that this emotion-focused parenting intervention contributed to improvement in parents’ emotion coaching and child externalizing problems, while children’s self-regulation showed mainly normative developmental improvements. Further research with a larger sample will be the next step to determine if these pilot findings are seen in an adequately powered study.